Exploring the Influence of Culture on Adherence to Physical Activity Guidelines Among Older Adults With Diabetes Mellitus and/or Chronic Kidney Disease in KSA: A Mixed Methods Study (Baltic Journal of Sport and Health Sciences, 2026)
Background: Physical activity is essential for managing chronic conditions such as diabetes mellitus (DM) and chronic kidney disease (CKD), especially among older adults. However, adherence to physical activity guidelines remains low, particularly in Saudi Arabia, where cultural norms and traditions may significantly influence engagement. While previous research has examined biomedical factors, limited studies have explored the role of cultural perceptions in shaping physical activity behaviours among this population.Aim: This study investigates the cultural influences on adherence to physical activity recommendations among older adults (aged 65 years and above) diagnosed with DM and/or CKD in Saudi Arabia, incorporating perspectives from both patients and their informal caregivers.Methods: A mixed-methods, sequential explanatory design was employed. The quantitative phase involved a cross-sectional survey assessing physical activity levels using the validated Arabic version of the Physical Activity Scale for the Elderly (PASE) (n = 256). The qualitative phase utilised dyadic interviews with older adults and their caregivers (n = 15 dyads) to explore cultural perceptions, facilitators, and barriers to physical activity adherence. Data were analysed using statistical methods for the quantitative phase and thematic analysis for qualitative findings.Preliminary Findings: Older adults in Saudi Arabia with DM and/or CKD reported low PA levels based on quantitative and qualitative findings. The mean PA score was 30.62, mostly from light housework (6.35) and caregiving (5.88). PA declined with age, with those 80+ scoring 86% lower than those aged 65–69 (p < 0.001). University-educated participants had 2.5 times higher PA than those with no formal education (p = 0.018). CKD patients were less active than those with DM (RR = 0.586, p = 0.038), and longer illness duration reduced PA. Qualitative findings showed PA was seen as part of daily life, influenced by gender roles, ageing norms, family protectiveness, and social expectations.Conclusion and Conference Presentation: This study provides novel insights into the cultural dimensions of physical activity adherence among older adults with DM and/or CKD KSA. Understanding these influences is crucial for developing culturally tailored interventions that promote physical activity in this population.Keywords: PA, culture, older adults, DM, CKD